2019
DOI: 10.1002/ajs4.65
|View full text |Cite
|
Sign up to set email alerts
|

Social cohesion in rural Australia: Framework for conformity or social justice?

Abstract: While social cohesion has become a commonly accepted policy goal and framework in many ethnically diverse soci-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 20 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…Stage Three of the project, on which this paper is focussed, involved collection of qualitative data, including 18 interviews with students based at La Trobe University’s Shepparton and Mildura campuses. Shepparton and Mildura are regional cities within the state of Victoria, with populations of slightly more than 50,000 (Australian Bureau of Statistics (ABS), 2017a, 2017b), with significant histories of migration and reputations for being multicultural regional cities, though they retain majority Anglo-Australian populations (Moran and Mallman, 2015). Both cities are served by a relatively small university campus.…”
Section: The Study and Methodologymentioning
confidence: 99%
“…Stage Three of the project, on which this paper is focussed, involved collection of qualitative data, including 18 interviews with students based at La Trobe University’s Shepparton and Mildura campuses. Shepparton and Mildura are regional cities within the state of Victoria, with populations of slightly more than 50,000 (Australian Bureau of Statistics (ABS), 2017a, 2017b), with significant histories of migration and reputations for being multicultural regional cities, though they retain majority Anglo-Australian populations (Moran and Mallman, 2015). Both cities are served by a relatively small university campus.…”
Section: The Study and Methodologymentioning
confidence: 99%
“…Here program participants spoke highly of their enjoyment of the program, whilst acknowledging that it had not changed any of the broader structural issues that participants said impacted upon their lives and reinforced their minority status (Stead, 2017). However, other research into social cohesion in two regional communities in Victoria found that local stakeholders felt that addressing structural concerns was an integral component of social cohesion (Moran & Mallman, 2019). Moran and Mallman (2019) indeed concluded that social cohesion does have the capacity to be delivered in a way that emphasises social justice and responds to structural issues, rather than promoting an underlying neoliberal agenda.…”
Section: Social Cohesionmentioning
confidence: 96%
“…However, other research into social cohesion in two regional communities in Victoria found that local stakeholders felt that addressing structural concerns was an integral component of social cohesion (Moran & Mallman, 2019). Moran and Mallman (2019) indeed concluded that social cohesion does have the capacity to be delivered in a way that emphasises social justice and responds to structural issues, rather than promoting an underlying neoliberal agenda.…”
Section: Social Cohesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in Australia reflects trends in other locations. Overlapping interests have been in the transformations of rural places through migration, which have been captured through various sociological concepts including social integration, belonging ( De Lima, 2012 ), and social cohesion (in Australia, Moran and Mallman, 2019 ), rural multiculturalism ( Wilding and Nunn, 2018 ) and rural cosmopolitanism ( Schech, 2014 ; Woods, 2018a ) (for which Woods (2018b) has identified early beginnings in late 19th and early 20th century Australia). Scholars in Europe and Australia have highlighted the interconnectedness of rural places with others through the concept “translocalism” ( De Lima, 2012 ) and “multi-local settlement” ( Boese et al 2020 ).…”
Section: Scholarship On Migrants’ and Refugees’ Regional Migration Experiences In Australia And Internationallymentioning
confidence: 99%